Antarctic Radiocarbon Reservoir: The case of the mummified crabeater seals (Lobodon carcinophaga) in Bodman Cape, Seymour Island, Antarctica - Negrete, Javier; Soibelzon, Esteban; Tonni, Eduardo Pedro; Carlini, Alejandro; Poljak, Sebastián; Huarte, Roberto Andrés; Carbonari, Jorge Eduardo (Radiocarbon)
At least 50% of the world’s seal population is distributed in the pack-ice region surrounding Antarctica. Among the Antarctic seals, Lobodon carcinophaga (commonly known as “crabeater seals”) are the most abundant. This is a krill-feeding species, subsisting primarily on Euphausia superba. The occurrence of mummified seals has been documented since 1900 in several Antarctic regions, and different hypotheses about age and what happened to them have been proposed. Taking into account the depletion of 14C concentration in marine waters, we dated a recently deceased and a mummified L. carcinophaga along with a mollusk (Nacella concinna) collected alive from different locations around Antarctica. We discuss their relationship in light of the 14C reservoir. The age obtained for the recently deceased crabeater seals suggests a reservoir age of around 1300 yr for these waters, which is in agreement with the correction value for reservoir age obtained for the same species in the area. We applied this reservoir correction value to the conventional age of 1180 14C yr BP obtained for the mummified seal. The results indicate that the death event probably occurred within the last 100 yr. The age obtained for the mollusk specimen confirms that the correction values of the reservoir effect for the Antarctic continent vary according to geographical location and to the type of sample dated. Fil: Negrete, Javier. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Soibelzon, Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Tonni, Eduardo Pedro. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina ...